Estudo da dinâmica de uma partícula submetida a forças resistivas do tipo linear e quadrática - SOUZA, Edenil Quaresma de (UNIFAP – Universidade Federal do Amapá, 2022)
In this Conclusion work of a specialization course in physics teaching, we analyze some aspects of the dynamics of the movement of a projectile in the vertical plane and short distance, considering that it interacts with two types of forces, the gravitational force, which is vertical and conservative and another that is due to the interaction of the projectile with the air particles (atmosphere) which results in a frictional force of dissipative nature. In the latter case we still consider the two forms of frictional force, one that is linearly proportional to the instantaneous velocity vector of the projectile and the other form where the frictional force is quadratically proportional to the vector of the instantaneous velocity of the projectile. In particular, we analyze how the projectile's mechanical energy dissipates in different parameters of the initial firing conditions, firing angle and initial velocity, in each case of the dissipative forms of the frictional forces.